2022
DOI: 10.1016/j.ejogrb.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and pregnancy: A comparison of case reports, case series and registry studies

Abstract: Background Selection, outcome and publication biases are well described in case reports and case series but may be less of a problem early in the appearance of a new disease when all cases might appear to be worth publishing. Objective To use a prospectively collected database of primary sources to compare the reporting of COVID-19 in pregnancy in case reports, case series and in registries over the first 8 months of the pandemic. Study Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 143 publications
0
10
0
Order By: Relevance
“…A PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) analysis of 149 studies found adverse outcomes to be more common in case reports and series suggesting reporting bias and raised concerns of patient overlap in registry studies. 4 The most recent update of a live global systematic review of COVID-19 infections in pregnancy included over 60,000 pregnant or recently pregnant women from 192 studies. Reported prevalence of pregnancy-associated infections ranging from 7% with universal sampling to 28% in symptomatic women.…”
Section: Epidemiology and Adverse Outcomes In Association With Pregna...mentioning
confidence: 99%
“…A PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) analysis of 149 studies found adverse outcomes to be more common in case reports and series suggesting reporting bias and raised concerns of patient overlap in registry studies. 4 The most recent update of a live global systematic review of COVID-19 infections in pregnancy included over 60,000 pregnant or recently pregnant women from 192 studies. Reported prevalence of pregnancy-associated infections ranging from 7% with universal sampling to 28% in symptomatic women.…”
Section: Epidemiology and Adverse Outcomes In Association With Pregna...mentioning
confidence: 99%
“…The World Health Organization announced that the outbreak of (COVID-19) can be considered a "pandemic" where the virus spreads progressively around the world. Thirty-nine million people and more suffered from the virus worldwide till Oct 16, 2020, with a death toll exceeding 1,099,000 [1][2][3][4][5]. The severe acute respiratory syndrome coronavirus-19 pandemic has uncovered vulnerable populations across international health crises [1,2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-nine million people and more suffered from the virus worldwide till Oct 16, 2020, with a death toll exceeding 1,099,000 [1][2][3][4][5]. The severe acute respiratory syndrome coronavirus-19 pandemic has uncovered vulnerable populations across international health crises [1,2,[6][7][8]. The knowledge obtained from prior human coronavirus epidemics revealed that pregnant women and neonates are from the most vulnerable populations and at high risk of COVID-19 infection, according to their body immunity and are mainly at risk for bad findings [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations